Asymptotic expansions of the distribution function of the sums of independent identically distributed non-lattice random vectors - Bikelis, A. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Бикялис. Асимптотические разложения для распределении сумм независимых случайных векторов A. Bikelis. Nepriklausomų vienodai pasiskirsčiusių nerėtinių atsitiktinių vektorių sumų pasiskirstymo funkcijų asimptotiniai išdėstymai